GOVERNMENT SUPPORT AND FINANCIAL PERFORMANCE POST-COVID-19: EVIDENCE FROM SMALL AND MEDIUM ENTERPRISES - Vang Quang Dang; Nguyen Khac Hieu (Фінансово-кредитна діяльність: проблеми теорії та практики)
Small and medium enterprises (SMEs) are vulnerable during the Covid-19 pandemic because they have limited resources. To prevent SMEs from going bankrupt after the Covid-19 pandemic, the government needs reasonable support policies for SMEs. This paper examines the impact of government support, including interest rate, tax, training, and consulting support, on the performance of SMEs post-COVID-19. We use Return on Assets (ROA), Return on Sales (ROS) and profit to represent the performance of SMEs. We have reviewed previous studies to propose a research model and questionnaire. Based on the questionnaire, we collected data from 355 SMEs in Vietnam by surveying in 2022. The OLS regression model was used to test the hypotheses in the research model. The results show that government support positively affects ROA, ROS and profit. Besides, SMEs that invest in new technologies, equipment or software have higher ROA and ROS and SMEs that obtain quality management system certificates such as ISO 9001 have better profits. Based on the research results, we have proposed solutions to support SMEs in overcoming crises like COVID-19. This result is crucial for policy-makers who want to allocate the government's limited budget to stimulate economic development.